High-dimensional immune phenotyping of blood cells by mass cytometry in patients infected with hepatitis C virus. (April 2022) - Herderschee, Jacobus; Heinonen, Tytti; Fenwick, Craig; Schrijver, Irene T.; Ohmiti, Khalid; Moradpour, Darius; Cavassini, Matthias; Pantaleo, Giuseppe; Roger, Thierry; Calandra, Thierry; ,; Aebi-Popp, K.; et al.
Abstract: Objectives: Chronic hepatitis C virus (HCV) infection affects the immune system. Whether elimination of HCV with direct-acting antivirals (DAA) restores immunity is unclear. We used mass cytometry to get a broad and in-depth assessment of blood cell populations of patients with chronic HCV before and after DAA therapy. Methods: Before and 12 weeks after sustained virological response (SVR12) to DAA therapy, 22 cell populations were analysed by mass cytometry in blood collected from ten healthy control individuals and 20 HCV-infected patients with (ten patients) or without (ten patients) human immunodeficiency virus (HIV) infection. Results: HCV infection altered the frequency of 14/22 (64%) blood cell populations. At baseline, the frequencies (median, interquartile range (IQR); control, HCV, HCV/HIV) of intermediate monocytes (1.2, IQR 0.47–1.46; 1.76, IQR 0.83–2.66; 0.78, IQR 0.28–1.77), non-classical monocytes (1.11, IQR 0.49–1.26; 0.9, IQR 0.18–0.99; 0.54, IQR 0.28–1.77), conventional dendritic cells type 2 (0.55, IQR 0.35–0.59; 0.31, IQR 0.16–0.38; 0.19, IQR 0.11–0.36) and CD56 dim natural killer cells (8.08, IQR 5.34–9.79; 4.72, IQR 2.59–6.05) 3.61, IQR 2.98–5.07) were reduced by 35% to 65%, particularly in HCV/HIV co-infected patients. In contrast, activated double-negative T cells (0.07, IQR 0.06–0.10; 0.10, IQR 0.09–0.19; 0.19, IQR 0.12–0.25), activated CD4 T cells (0.28, IQR 0.21–0.36; 0.56, IQR 0.33–0.77; 0.40, IQR 0.22–0.53) and activated CD8 T cells (0.23, IQR 0.14–0.42; 0.74, IQR 0.30–1.65; 0.80, IQR 0.58–1.16) were increased 1.4 to 3.5 times. Upon stimulation with Toll-like receptor ligands, the expression of cytokines was up-regulated in 7/9 (78%) and 17/19 (89%) of the conditions in HCV- and HCV/HIV-infected patients, respectively. Most alterations persisted at SVR12. Conclusions: Chronic HCV and HCV/HIV infections induce profound and durable perturbations of innate and adaptive immune homeostasis. Graphical abstract: Image 1